ANALISIS STRUKTUR, PERILAKU DAN KINERJA AGROINDUSTRI INDONESIA: Suatu Catatan Empiris - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
In Indonesia, deepening of the industrial structure and stengthening of interindustry linkages have been major objectives of industrialization since Repelita IV. This article examines the structure, conduct, and performance of the Indonesian agroindustry sector. Agroindustry is defined broadly, as not only agro-processing industries and agro-input supplier industries, but also all subsectors in the agricultural sector. The interindustry linkage analysis shows that agroindustries have both high forward and backward linkages. This is consistent with conduct analysis that proved those subsectors have relatively high output multipliers. The income and employment multipliers indicate that almost all agroprocessing industries brought high multiplier effects. The concentration ratios, using CR4, for the agroindustry tend to decrease from time to time, although they vary considerably. The ratios are far lower than those of the average manufacturing industry. Yet, there are four agroindustry subsectors in which concentration ratios tend to increase, i.e. the food industry, cigarette industry, textile industry, and leather industry. Export dependency ratios reveal there is a tremendous change in agroindustrial performance. This is supported by Spearman rank correlation coefficients that are quite significant. As far as structural transformation is concerned, this study concludes that the evidence of structural transformation between1980 and 1990 does not prevail.